PENGARUH PERSEPSI RISIKO, PERSEPSI PRIVASI, PERSEPSI KEAMANAN DAN LITERASI KEUANGAN TERHADAP MINAT MENGGUNAKAN FINANCIAL TECHNOLOGY (FINTECH) PADA MAHASISWA AKUNTANSI - Fikri, Akmal (Jurusan Akuntansi FEB UNTAN, 2024)
This research aims to determine whether risk perception, privacy perception, security perception, and financial literacy influence the interest in using financial technology (fintech) among accounting students at the Faculty of Economics and Business, Universitas Tanjungpura (FEB Untan). This study employs a quantitative approach with a sample size of 100 respondents. The sampling technique utilized in this research is purposive sampling. The analysis method employed is multiple linear regression analysis, which aims to determine the extent of the influence of independent variables (X) on the dependent variable (Y). Primary data collection is conducted through a questionnaire survey. The results of the analysis indicate that risk perception and privacy perception do not have a significant impact on the interest in using fintech among FEB Untan accounting students. However, security perception and financial literacy significantly influence the interest in using fintech among FEB Untan students.